Measurement of Performance Efficiency of Kadatuan Koffie Suppliers Using Data Envelopment Analysis (DEA) - Rahmah, Devi Maulida; Fadhlurrahmah, Jauhar; Pujianto, Totok; Ardiansah, Irfan; Mardawati, Efri (Department of Agro-industrial Technology, University of Brawijaya, 2020)
AbstractHigher market expectation towards coffee products both of its quantity and quality is one of several challenges currently faced by the coffee industry. Maintaining the coffee supply chain through a periodical evaluation of supply chain performance, therefore, is crucial. The research provided measurement of performance efficiency of Kadatuan Koffie company’s suppliers using Data Envelopment Analysis (DEA). This measurement is required to know the supplier’s level of performance efficiency as a consideration in conducting the company’s raw material management. Management of supplier’s activity is essential to maintain the flow of supply chain running smoothly. The data obtained in this research were interview results with farmers or suppliers of raw material or coffee beans for Kadatuan Koffie and the company’s management. The data were processed using DEA by comparing output and input value. According to the measurement of performance efficiency towards seven suppliers of Kadatuan Koffie, three of them are categorized as efficient, namely the farmer in Cimaung, Cibodas and Dago that showed an efficiency value of 1.Keywords: Data Envelopment Analysis, performance efficiency, supplier